Evaluation of Cytotoxic Effect of Silver Nanoparticles (AgNP) Synthesized from Phlebodium aureum (L.) J. Smith Extracts - Marimuthu, Johnson; Thangaiah, Shibila; Santhanam, Amutha; George, Vidyarani (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Chemical synthesis methods are adverse in the medicinal field as they produce toxins on the surface area whereas green synthesis provide advancement are cost effective, environment friendly, can be easily scaled up for large scale synthesis. Silver and silver nanoparticles have an important application in the medical industry, such as tropical ointments which are used to prevent infection against burn and open wounds. There is no report on the green synthesis from Phlebodium aureum (L.) J. Smith. Objective: The present study was aimed to synthesize silver nano-particles using Phlebodium aureum (L.) J. Smith extracts by green approach and to screen their cytotoxicity. Methods: The synthesized AgNPs of P. aureum were characterized by FT-IR, SEM and XRD. The cytotoxicity of the aqueous extracts and AgNPs of P. aureum was determined. Results: The silver nanoparticle synthesis was confirmed by color change from yellow to dark brown and absorption peak at 460 nm. FT-IR analysis confirmed the capping by proteins and other metabolites. XRD analysis confirmed the existence of silver nanaoparticles with a peak at 46.253°. The dose dependent cytotoxicity was observed in the aqueous and silver nanoparticles of P.aureum. Conclusion: The present study gave a simple and cheap route to synthesize the AgNPs using aqueous extracts of P. aureum. The studied extracts of P. aureum can be considered as a promising candidate for a plant-derived anti-tumour compound.
Keywords: P. aureum